1997
DOI: 10.1063/1.366204
|View full text |Cite
|
Sign up to set email alerts
|

Profile simulation of conformality of chemical vapor deposited copper in subquarter-micron trench and via structures

Abstract: Copper profile evolution in ultralarge scale integration via and trench structures was investigated for thermal low pressure, low temperature, chemical vapor deposition (LPCVD) from CuI(tmvs)(hfac). The investigation examined copper profiles in specialized cantilever structures as a function of systematic changes in key processing conditions, namely, substrate temperature, precursor flux, and hydrogen reactant flow. Resulting experimental observations from cross section scanning electron microscopy were incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…This can, in part, be explained by the wide range of methods used to determine the probabilities, ranging from ab initio density functional theory calculations 9 to direct beam experiments, 14 but also by variations in experimental and theoretical accuracies. Temperaturedependent values of s have also been reported; for example, an increase in s with temperature was found for Hf͑NEtMe͒ 4 and Ti͑O i Pr͒ 4 precursor adsorption. 15,16 Regarding the reactant step in plasma-assisted ALD, oxygen radicals appear the most reactive, whereas hydrogen radicals have generally the lowest reactivity.…”
Section: Plasma-assisted Aldmentioning
confidence: 85%
See 1 more Smart Citation
“…This can, in part, be explained by the wide range of methods used to determine the probabilities, ranging from ab initio density functional theory calculations 9 to direct beam experiments, 14 but also by variations in experimental and theoretical accuracies. Temperaturedependent values of s have also been reported; for example, an increase in s with temperature was found for Hf͑NEtMe͒ 4 and Ti͑O i Pr͒ 4 precursor adsorption. 15,16 Regarding the reactant step in plasma-assisted ALD, oxygen radicals appear the most reactive, whereas hydrogen radicals have generally the lowest reactivity.…”
Section: Plasma-assisted Aldmentioning
confidence: 85%
“…For example, for chemical vapor deposition, simulations are numerous and have been used to study many aspects of the deposition process including the conformality that can be achieved by various processes. 4,5 For thermal ALD, a number of theoretical studies regarding conformality have been reported in the literature.…”
mentioning
confidence: 99%
“…On the other hand, the reemission depends indirectly on many deposition parameters, such as temperature, precursor partial pressure, reactant gas flow, etc. [18,19]. More conformal filling means more re-emission events occur till the precursor molecule will react with the growing film surface.…”
Section: Discussionmentioning
confidence: 97%
“…3a) and the most porous films (highest deposition rate) cannot fill the holes at all. Burke et al [18] have shown that re-emission and surface diffusion are responsible for conformal filling of three dimensional structures by copper. Surface diffusion is a temperature related process and it is significant only at higher temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…The enhancement of precursor concentration can be achieved by increasing the precursor partial pressure in the reaction zone by the increase of the precursor flow while keeping all other process parameters fixed. The partial pressure of precursor (P precursor ) is defined as follows: 17,18) …”
Section: Deposition Characteristicsmentioning
confidence: 99%